Preparation of LLM‐105‐Based Explosive Ink and Its Detonating Transfer Performance in Explosive Network. Issue 9 (30th June 2022) - Cai, Jialin; Luo, Guan; Huang, Hui; Liu, Yousong; Di, Xin; Gao, Han
Abstract: A new explosive ink based on 2, 6‐diamino‐3, 5‐dinitropyrazine‐1‐oxide (LLM‐105) was designed and prepared. The explosive ink was deposited into micro‐size grooves by using direct ink writing (DIW) technology and its detonation properties in an explosive network were explored. The properties of impact sensitivity, detonation velocity and critical size of detonation were determined and analyzed. The results show that this explosive has a good impact safety. When the LLM‐105 content is 88 % and the density is 95 % TMD, the detonation velocity and critical size of detonation values are 7, 771 m/s and 0.5×0.5 mm respectively. Moreover detonation velocity results indicated the explosive ink in micro‐size grooves loaded by DIW was uniform. Abstract :